Hydrophilic Copolymers with Hydroxamic Acid Groups as a Protective Biocompatible Coating of Maghemite Nanoparticles: Synthesis, Physico-Chemical Characterization and MRI Biodistribution Study - Hana Charvátová; Zdeněk Plichta; Jiřina Hromádková; Vít Herynek; Michal Babič (MDPI AG, 2023)
Superparamagnetic iron oxide nanoparticles (SPION) with a "non-fouling" surface represent a versatile group of biocompatible nanomaterials valuable for medical diagnostics, including oncology. In our study we present a synthesis of novel maghemite (γ-Fe2O3) nanoparticles with positive and negative overall surface charge and their coating by copolymer P(HPMA-co-HAO) prepared by RAFT (reversible addition-fragmentation chain-transfer) copolymerization of N-(2-hydroxypropyl)methacrylamide (HPMA) with N-[2-(hydroxyamino)-2-oxo-ethyl]-2-methyl-prop-2-enamide (HAO). Coating was realized via hydroxamic acid groups of the HAO comonomer units with a strong affinity to maghemite. Dynamic light scattering (DLS) demonstrated high colloidal stability of the coated particles in a wide pH range, high ionic strength, and the presence of phosphate buffer (PBS) and serum albumin (BSE). Transmission electron microscopy (TEM) images show a narrow size distribution and spheroid shape. Alternative coatings were prepared by copolymerization of HPMA with methyl 2-(2-methylprop-2-enoylamino)acetate (MMA) and further post-polymerization modification with hydroxamic acid groups, carboxylic acid and primary-amino functionalities. Nevertheless, their colloidal stability was worse in comparison with P(HPMA-co-HAO). Additionally, P(HPMA-co-HAO)-coated nanoparticles were subjected to a bio-distribution study in mice. They were cleared from the blood stream by the liver relatively slowly, and their half-life in the liver depended on their charge; nevertheless, both cationic and anionic particles revealed a much shorter metabolic clearance rate than that of commercially available ferucarbotran.